Determination Of Local Own-Source Revenue (Pad) In Districts And Cities Across East Java Province In 2020-2021 - INDIRASWARI, Susmita Dian (Journal of Tourism Economics and Policy, 2024)
This study aims to determine the effect of regional tax revenues, regional levies and results of separated regional wealth management on local own-source revenue (PAD) in regencies and cities throughout East Java in 2020-2021, either partially or simultaneously. This study uses a quantitative approach with multiple linear regression analysis methods, classical assumption tests, hypothesis testing and coefficient determination (R2). The results of this study show that simultaneously (test f) local taxes, regional fees and the results of regional wealth management which are decided to affect regional original income (PAD) in Regencies and Cities throughout East Java in 2020-2021. Meanwhile, partially (t test) the regional tax variable has an effect on regional original income (PAD) in Regencies and Cities throughout East Java in 2020-2021. The regional retribution variable has a positive effect on regional original income (PAD) in Regencies and Cities throughout East Java in 2020-2021. Meanwhile, the results of separated regional wealth management have no effect on regional original income (PAD) in regencies and cities throughout East Java in 2020-2021.